L-Shape Steel Slag Filter Phosphorus Removal: A Perfomance Study: A perfomance study - Ramli, Norazizan; Hamdan, Rafidah (Recent Trends in Civil Engineering and Built Environment, 2021)
Phosphorus can often be found in domestic wastewater effluent as the existing conventional treatment system was not designed for its removal. The presence of phosphorus in the final discharge of wastewater will create an environmental problem that is eutrophication. To reduce this problem, alternative domestic wastewater treatment is needed. Therefore, this study aimed to design a lab-scale L-shape semi aerated steel slag filter designed to remove phosphorus from domestic wastewater. Steel slag has been used as a filter medium to enhance phosphorus removal due to the Ca, Al, and Mg contents as it has a high potential in adsorbing phosphorus from domestic wastewater. The lab-scale L-shaped semi aerated steel slag filter system has been set up in the MPRC laboratory, UTHM. To run the L-shape aerated steel slag filter, which combines an aerated vertical and unaerated horizontal filter, domestic wastewater was collected from UTHM Sewerage Treatment Plant influent. The effectiveness of the system in removing phosphorus was monitored for three weeks by analyzing the wastewater influent and effluent of the vertical and horizontal filter twice a week for pH, turbidity, Dissolved Oxygen (DO), and Total P. From the study, the pH value obtained was in alkaline condition, DO range from 7.52 to 7.93 mg/L due to aeration system in the vertical filter and range from 7.58 to 7.84 mg/L in the horizontal filter. The system has been able to remove turbidity effectively range from 29.73 to 3.6 NTU. The phosphorus removal efficiency in L-shape semi aerated steel slag filter range from 1.13 to 0.95. In conclusion, the L-shape semi aerated steel slag filter can remove phosphorus from domestic wastewater, and the design of the system should be improvised.